Physicochemical Properties of Bread Partially Substituted with Unripe Green Banana (Cavendish spp.) Flour - Pakathip Thakaeng; Thitirat Boonloom; Saroat Rawdkuen (Molecules, 2021)
This study aimed to utilize unripe green bananas obtained from those that were graded as unacceptable for export. Bread was selected as the product model for the application of banana flour. As carbohydrates and other functional active compounds make up the main composition of green bananas, unripe banana flour (UBF) was prepared and characterized. The chemical composition, physico-chemical properties, and functional properties of UBF, as well as its application in bread for wheat flour (WF) substitution at different levels, were investigated. Quality attributes of the bread were determined. High carbohydrate (89%), total dietary fiber (7%), ash (2%), potassium content and radical scavenging activity were found in UBF bread, while protein (15%) and fat contents (0.9%) were higher in WF bread (p < 0.05). Starch granules of different sizes and shapes (round, long and oblong) were observed in the starch from UBF bread. Solubility, swelling power, and the water absorption capacity of WF bread were greater than UBF bread (p < 0.05). The gelatinization enthalpy (ΔH) was 0.69 and 5.00 J/g for WF and UBF, respectively. The rapid viscoanalyzer (RVA) pasting profile showed that UBF bread had a higher pasting temperature, peak viscosity, breakdown, and final viscosity than WF bread (p < 0.05). Increasing the level of UBF caused an increase in bread hardness and a decrease in loaf volume (p < 0.05). We show that UBF can be considered a value-added product with health-promoting properties. The utilization of UBF as a functional food ingredient will benefit the consumer.